Smooth switching in a scheduled robust model predictive controller. (July 2015) - Khani, Fatemeh; Haeri, Mohammad
Abstract : Highlights: A scheduled RMPC with local controllers is proposed to control nonlinear systems. The proposed method enlarges the domain of attraction efficiently. The proposed RMPC is then modified to handle the transient response problem. This approach does not complicate the controller implementation considerably. Stability of the closed loop system is guaranteed. Abstract: This paper proposes a bumpless transfer method to overcome the problem of switching jumps in a scheduled robust model predictive control approach. A scheduled robust model predictive controller implements a set of local robust model predictive controllers based on an on-line switching strategy. This method could enlarge the domain of attraction efficiently but the transient response might be hampered by spikes appearing at the moment of switching between adjacent local controllers. The proposed algorithm could enhance the transient response by implementing some intermediate controllers augmented to the main control scheme to solve the problem without needing more computation. The efficiency of the proposed algorithm is illustrated with two examples.